Women's Sports Needs in Wasit Governorate: Challenges of Participation and Opportunities for Physical Activities - Hamid Hussein Thaban (Penerbit Jurnal Indonesia, 2025)
This study aims to analyze the sporting needs of women in Wasit Governorate, focusing on the challenges hindering their participation in physical activities and the opportunities available to enhance this participation, with a particular focus on the Youth Forum Center affiliated with the Ministry of Youth and Sports in Al-Nu'maniyah. The study adopted a descriptive approach to ensure a thorough and accurate analysis, with a sample of 150 women who frequent the center. Data were collected using various tools, including questionnaires and personal interviews, to gain a deep understanding of the challenges and needs. The results showed that socio-cultural barriers constitute the greatest challenge (70%), with traditional norms and expectations of gender roles playing a significant role in limiting women's participation in sports. The results also indicated that religious barriers (60%), often associated with strict interpretations of norms, and security challenges (55%), such as the lack of safe facilities, negatively impact participation. In addition, the lack of dedicated sports facilities was identified as a major obstacle (50%), reflecting the weak infrastructure in the region. On the other hand, the study revealed promising opportunities, such as the Youth Forum programs that offer diverse sports activities, and university programs that support female students' participation in sports. These opportunities form a foundation upon which to build in order to enhance sports participation. Based on these findings, the study recommends activating dedicated women's sports courses within the framework of the Forum, with a focus on designing training programs that meet the needs of women of different age groups. It also recommends improving infrastructure by establishing safe and well-equipped sports facilities, especially in areas lacking such facilities. In addition, it suggests organizing awareness campaigns to change negative social and cultural perceptions about women's participation in sports, utilizing social media and community workshops. The study also emphasizes the importance of partnerships with sports clubs and local institutions to provide the necessary financial and technical support. These recommendations aim to promote women's participation in physical activities, contributing to their empowerment and improving their quality of life. The study provides a comprehensive overview of sports needs in Wasit Governorate, highlighting the importance of investing in infrastructure and raising awareness to overcome challenges and capitalize on available opportunities.